2009
DOI: 10.1083/jcb1864oia7
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of PIM serine/threonine kinases in FLT3-ITD–induced leukemogenesis reveals PIM1 as regulator of CXCL12–CXCR4-mediated homing and migration

Abstract: CORRESPONDENCE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 18 publications
2
59
0
3
Order By: Relevance
“…30 We and others have previously shown that transplantation of retroviral FLT3-ITD expressing progenitors can cause a myeloproliferative disease in vivo. 14,15 In contrast to those experiments, we here transplanted in vitro selected and expanded progenitors. As shown in Figures 1B and 2, expression of FLT3-ITD alone resulted in a poor selfrenewal capacity and was associated with differentiation of bone marrow progenitors towards monocytes/ macrophages and mast cells, which most probably abrogated their leukemogenic potential in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 We and others have previously shown that transplantation of retroviral FLT3-ITD expressing progenitors can cause a myeloproliferative disease in vivo. 14,15 In contrast to those experiments, we here transplanted in vitro selected and expanded progenitors. As shown in Figures 1B and 2, expression of FLT3-ITD alone resulted in a poor selfrenewal capacity and was associated with differentiation of bone marrow progenitors towards monocytes/ macrophages and mast cells, which most probably abrogated their leukemogenic potential in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…15,23 In vitro transduction, proliferation and immortalization assays 1.5 × 10 5 lineage-surface marker negative (Lin-) bone marrow cells (MagCellect Kit, R&D systems, Minneapolis, USA) from 6-10 week old Balb/C or C57BL/6 mice were transduced with retrovirus on a 48-well fibronectin-coated plate according to the manufacturer's protocol (Retronectin TM , TaKaRa, Bio Inc., Shiga, Japan). The cells were selected with neomycin (0.8 mg/mL, Life Technologies, Paisley, UK) and cultured in medium containing murine stem cell factor (mSCF), FLT3 ligand, IL-11, thrombopoietin (PeproTech, Rocky Hill, NJ, USA).…”
Section: Retroviral Expression Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pim1 knockout mice displayed defects in hematopoietic stem cell (HSC) homing to the bone marrow and the spleen by downregulation of the CXCR4 surface expression. Furthermore, PIM kinase inhibition in primary AML blasts induced downregulation of the CXCR4 receptor on the cell surface and PIM1 transcript levels correlated with CXCR4 surface expression in AML (37).…”
Section: Introductionmentioning
confidence: 99%
“…Another promising strategy would be to target pathways that regulate receptor recycling. A recent paper (Grundler et al, 2009) suggests that PIM kinase mediates surface expression of CXCR4, which suggests that targeting PIM/FLT3 would be a more efficient therapy for targeting the bone marrow microenvironment. Thus, the use of CXCR4 inhibitors may be a potentially useful approach to overriding stromalmediated chemoresistance.…”
Section: Targeting Bone Marrow Microenvironmentmentioning
confidence: 99%